1986
DOI: 10.1039/p29860002045
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of polar effects. Part 15. Ionisation and esterification with diazodiphenylmethane of [2.2]paracyclophane-4-carboxylic acid and its pseudo-bromo-substituted derivatives, and the alkaline hydrolysis of their methyl esters

Abstract: lchester C04 3S0, EssexThe pK, values of [2.2] paracyclophane-4-carboxylic acid and its four pseudo-bromo-su bstituted derivatives have been determined in 80% (w/w) 2-methoxyethanol-water at 25 "C. The rate coefficients for the esterification of these acids with diazodiphenylmethane have been measured in 2methoxyethanol at 30 "C. The rate coefficients for the alkaline hydrolysis of the corresponding methyl esters have been determined in 70% (v/v) dimethyl sulphoxide-water at both 56.3 and 76.3 "C. In the ionis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Tentatively, steric inhibition of solvation could be considered. Actually, it has been demonstrated that the solvation inhibition goes hand in hand with the steric effect increases and appears to be very pronounced for tert ‐butyl and 2,6‐dimethyl substituents 30, 37–39. Esters, when protonated, form bulky carbocations having high steric inhibition to solvation, whereas the flat tert ‐butyl carbocation, formed by alkyl cleavage, can be easier to solvate, thanks to its planar configuration.…”
Section: Resultsmentioning
confidence: 99%
“…Tentatively, steric inhibition of solvation could be considered. Actually, it has been demonstrated that the solvation inhibition goes hand in hand with the steric effect increases and appears to be very pronounced for tert ‐butyl and 2,6‐dimethyl substituents 30, 37–39. Esters, when protonated, form bulky carbocations having high steric inhibition to solvation, whereas the flat tert ‐butyl carbocation, formed by alkyl cleavage, can be easier to solvate, thanks to its planar configuration.…”
Section: Resultsmentioning
confidence: 99%